(1/3+1/3x)/(1/x+1/3)
Numerator = 1/3+1/3x
= x/3x + 1/3x = (x + 1)/3x
Denominator = 1/x+1/3
= 3/3x + x/3x
= (x + 3)/3x
Therefore numerator / denominator
= [(x + 1)/3x]/[(x + 3)/3x]
= [(x + 1)/3x] * [3x/(x + 3)]
= (x + 1)/(x + 3)
2006-11-18 12:20:26
·
answer #1
·
answered by Wal C 6
·
0⤊
0⤋
Use FOIL i.e. First Terms, Outer terms, Inner Terms, Last Terms. Multiply the corresponding terms together and add. List terms in order of highest exponents. I prefer using fractions myself but when doing problems here, I find that using decimals is less cumbersome.
.33*1/x=1/3x
.33*.33=.111
1/3x*1/x=1/3x^2
1/3x*1/3=1/9x
____________
1/3x^2+4/9x+.111
.111=1/9
1/3x^2+4/9x+1/9
Hope this helps.
2006-11-18 20:22:42
·
answer #2
·
answered by R. D 2
·
0⤊
1⤋
Let's get everything inside the parens over common denominators first:
(1/3 + 1/3x) = (x/3x + 1/3x) = (x+1) / 3x
(1/x + 1/3) = (3/3x + x/3x) = (3+x) / 3x
Now we can put these over each other and see what happens:
(x+1) / 3x
-------------- =
(3+x) / 3x
(x+1) / (3+x)
Hope that helps!
~ ⥠~
2006-11-18 20:17:45
·
answer #3
·
answered by I ♥ AUG 6
·
0⤊
1⤋
use foil
inside inside, inside outside, outside inside, outside outside
so 1/3 * 1/x + 1/3 * 1/3 + 1/3x * 1/x + 1/3x * 1/3
2006-11-18 20:17:01
·
answer #4
·
answered by Kate 3
·
0⤊
2⤋
(1/3 - 1/3 + 1/3x) / (1/3 - 1/3 + 1/x) = 1/3x / 1/x
\\subtract 1/3 from each
1/3x * 3 / 1/x * 3 = 3/3x / 3/x
\\multiply each by 3
(3/3x * 3x/1) / (3/x * 3x/1) = (9x / 3x) / (9x / x)
\\multiply each by 3x over 1
(9/x / 3x) / (9x/x) = (9/3) / (9/1) = 3/9 = 1/3
2006-11-18 20:52:15
·
answer #5
·
answered by mailrick12 3
·
0⤊
0⤋
(1/3+1/3x)/(1/x+1/3)
Remember BODMAS (Brackets Over Division Multiplication Addition Subtraction).
First work out the answer to 1/3. (0.33333333etc.)
0.3/0.3x/1/x+0.3
I'm presuming 1/3x means 0.3 times x?
Good luck.
2006-11-18 20:18:46
·
answer #6
·
answered by Anonymous
·
0⤊
1⤋
(1/3+1/3x)/(1/x+1/3) = [(x + 1)/3x]/[(3 + x)/3x]
= [(x + 1)/3x]*[3x/(3+x)]
= (x+1)/(3+x)
2006-11-18 21:05:44
·
answer #7
·
answered by Akilesh - Internet Undertaker 7
·
0⤊
1⤋
blueeeeeeeeeee,
i told u before
it is
(x/3x+1/3x)/(3/3x+x/3x)=
=(x+1)/(x+3)
2006-11-18 20:20:28
·
answer #8
·
answered by tadalos 3
·
0⤊
0⤋
follow order tionsof opera
2006-11-18 21:22:54
·
answer #9
·
answered by sweetmsgirl22_23 1
·
0⤊
0⤋
ask a teacher, go to ask.com or google
2006-11-18 20:21:43
·
answer #10
·
answered by aleiva_ musica! 2
·
0⤊
1⤋